Evaluación de diferentes formas de fertilización sobre la calidad de plántulas y el contenido de nitrógeno (N), fósforo (P) y potasio (K) en la producción de Ochroma pyramidale (Cav. ex Lam.) Urb. (balsa) a nivel de vivero - Parrales Carreño, Ginger Julissa (2022)
The present investigation was carried out in the forest nursery "El Almendro" located in the San Felipe precinct of the Mocache canton, province of Los Ríos. The objective of this research was to evaluate the different forms of fertilization on the quality of Ochroma pyramidale seedlings and the content of Nitrogen (N), Phosphorus (P) and potassium (K).